Effects of the lockdown on the mental health of the general population during the COVID-19 pandemic in Italy: Results from the COMET collaborative network - Andrea Fiorillo; Gaia Sampogna; Vincenzo Giallonardo; Valeria Del Vecchio; Mario Luciano; Umberto Albert; Claudia Carmassi; Giuseppe Carrà; Francesca Cirulli; Bernardo Dell’Osso; Maria Giulia Nanni; Maurizio Pompili; et al. (European Psychiatry, 2020)
Abstract